Genetic improvement of mungbean and urdbean and their role in enhancing pulse production in India - Singh, D. P.; Singh, B. B.; Pratap, Aditya (The Indian Journal of Genetics and Plant Breeding, 2017)
The initial varietal development in mungbean and urdbean focused mainly on selection from landraces or the germplasm samples collected, purified and evaluated. However, systematic efforts were made by National Agricultural Research System comprising Indian Council of Agricultural Research and State Agricultural Universities through All India Coordinated Pulses Improvement Project for varietal improvement. National Bureau of Plant Genetic Resources and AICPIP centres collected over 8,000 Vigna genetic resources and also introduced germplasm from other countries and made them available for evaluation. Several resistant donors were identified and used to transfer gene(s) for biotic stresses. As a result, a number of high yielding varieties were developed through intraspecific hybridization. Large numbers of these varieties are resistant to one or more major diseases of the specific agro-eclogical niches. Six varieties in mungbean and two in urdbean were also developed through inter-specific hybridization which had new plant type and resistance to prevalent diseases. However, limited success has been achieved for the development of varieties with resistance to insect-pests and abiotic stresses. There is a need to intensify research in these areas through introgression of desirable alleles from secondary and tertiary gene pool into the cultivated type for yield, photo period and temperature insensivity and insect pest tolerance. The onset of genomics provides massive amount of information, but the success will depend on precise phenotyping to achieve desired restructuring in existing plant type.